Inorganic analysis using CE: advanced methodologies to face old challenges - Kubáň, Petr; Timerbaev, Andrei R (Electrophoresis, 2014)
Inorganic species still remain of secondary importance when CE is used as an analytical separation tool. Despite considerable efforts of great many groups over last 20 years, plenty of competition, mostly from ion chromatography and elemental MS, restrains the routine use of CE in inorganic analysis. If there is yet hope clinging to make CE a viable alternative in the field, success would ultimately be attained through research activities on negating the disadvantages and amplifying the advantages of the method. Being the latest update of a series of reviews covering the time period from 1990 to 2010, this paper will comment on how and to what extent these challenges of inorganic CE analysis have been addressed in two recent years.
Keywords: anorganické látky; ionty; CE; Microchip electrophoresis; Ions; Inorganic ion analysis; Electrophoresis, Capillary; elektroforéza kapilární; Inorganic Chemicals